Macroeconomic Stability of The Romanian Industry Indicators - Mihaela Adina MATEESCU; Mihai Sabin MUSCALU; Elena Manuela ISTOC; Daniela Nicoleta BALEANU (Communications of International Proceedings, 2022)
This paper presents a study on the analysis of stability indicators in Romanian industry by two methods.  One is based on the classical methods to determine the models and to optimize the criterion functions describe the relationships between the indicators. The second method is based on the following idea: once a certain level of the macroeconomic stability is reached, this leads to a sustainable development of the industry and therefore to a stabilization of the indicators that characterize it.
Keywords: macroeconomic stability; indicators; sustainable development; modeling; optimization